2017
DOI: 10.17221/4/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Differences in size and architecture of the potato cultivars root system and their tolerance to drought stress

Abstract: Drought can cause substantial yield losses, particularly for crops with shallow root systems, such as potato (Solanum tuberosum). This study tested whether root system architecture could affect potato yield under drought conditions. The following parameters of the roots were measured: depth range, total length, total area, surface area, average diameter, and total dry weight of the root system. These parameters in soil layers were also measured at different depths. Five potato cultivars from a group of mid-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Potato cultivars exhibiting higher root to shoot ratio owing to extensive and large root architecture have been found to be less susceptible to drought stress as they can increase nutrient and water uptake efficiency (Wishart et al, 2013; Villordon et al, 2014; Zarzynska et al, 2017). Zarzynska et al (2017) tested five potato cultivars and reported a correlation between root length and area to tuber yield under drought stress. They concluded that potato cultivars with deeper root length and larger root systems exhibit increased drought tolerance.…”
Section: Drought Adaptation Strategiesmentioning
confidence: 99%
“…Potato cultivars exhibiting higher root to shoot ratio owing to extensive and large root architecture have been found to be less susceptible to drought stress as they can increase nutrient and water uptake efficiency (Wishart et al, 2013; Villordon et al, 2014; Zarzynska et al, 2017). Zarzynska et al (2017) tested five potato cultivars and reported a correlation between root length and area to tuber yield under drought stress. They concluded that potato cultivars with deeper root length and larger root systems exhibit increased drought tolerance.…”
Section: Drought Adaptation Strategiesmentioning
confidence: 99%
“…The plants were grown in a sandy substrate (87.2% sand, 9.3% silt, and 3.5% clay) extracted from the fields of one of our partner producers (Lac Saint-Jean, QC, Canada) in cylindrical pots of 45 cm in diameter and 37 cm in height. This height was sufficient to allow an adequate development of the roots since the root system of potato is mainly concentrated in the first 30 cm of soil (Lahlou and Ledent, 2005;Zarzyńska et al, 2017).…”
Section: Greenhouse Configuration and Cultivation Managementmentioning
confidence: 99%
“…The potato crop, because of its shallow root system, is sensitive to drought (Joshi et al, 2016;Zarzyńska et al, 2017;Dahal et al, 2019). Its root system has a lower efficiency compared to other crops and a low capacity to extract water and mineral salts from the soil (Steyn et al, 1998;Dechassa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Potato is consumed by humans under many different preparations-boiled, baked, fried, snack, chips, starch-and is a significant source of carbohydrates [3,4], protein [3,5,6], minerals [6], vitamin C [4], and phenolic compounds [6]. Potato crop is very sensitive to water stress [7][8][9], nitrogen fertilizer deficiency, and is subject to a wide variety of disorders and diseases. Aboveground disorders and diseases include early blight (Alternaria solani), late blight (Phytophthora infestans), Fusarium dry rot (Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%